Paham Keagamaan K.H Muhammad Zein bin Abdul Rauf (Kajian Filologis Naskah Kitab Kurratu Al-Ain Al-Fard Al-Ain) - Rasidin, Mr (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2007)
This Article aim to analyse idea of K. H. Muhammad Zein Abdul Rauf bin. In his article he studies three religion main problems namely tauhid, science, bahavior and.fiqh. In thefeld of tauhid science he studies the nature oJ obligation which is called wajib, mustahil (irnposible) ancl have to Allah SLVT. So also to nature of which is obligecl to be, irnposible and have to be for rasul, religion foundation and meaning it the ttvo confessions. In the feld of fiqih he studies aboul taharah, fasting and sholctt. While in the feld of behavior he studies about immoral related to orgon which is zahir (organ irnrnoral lahiriah) and wich is rnind (batiniah) and also the nature of the nature the praised attributed attached to all mukallaf.